Heat dissipation analysis of electronic equipment based on CFD. (August 2019) - Liu, Xianlong; Tang, Song; Feng, Mei
Abstract: In order to quantitatively analyze the heat dissipation of high-power devices, Icepak software is used for analysis. Comparing the effects of fans on heat dissipation, two models were established respectively (with fan and without fan). Combining the advantages of Icepak, the grid around the radiator is combined with structured and unstructured grid. Through the analysis, the maximum temperature decreases by 22.2°C and 36.6% when there is a fan (the flow rate is 0.003kg/s).